2014
DOI: 10.1002/anie.201407145
|View full text |Cite
|
Sign up to set email alerts
|

Insect‐Derived Proline‐Rich Antimicrobial Peptides Kill Bacteria by Inhibiting Bacterial Protein Translation at the 70 S Ribosome

Abstract: Proline-rich antimicrobial peptides (PrAMPs) have been investigated and optimized by several research groups and companies as promising lead compounds to treat systemic infections caused by Gram-negative bacteria. PrAMPs, such as apidaecins and oncocins, enter the bacteria and kill them apparently through inhibition of specific targets without a lytic effect on the membranes. Both apidaecins and oncocins were shown to bind with nanomolar dissociation constants to the 70S ribosome. In apidaecins, at least the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
258
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(283 citation statements)
references
References 25 publications
23
258
1
1
Order By: Relevance
“…Chex1-Arg20 possesses high sequence homology to all oncocins, with the 10-residue sequence PYLPRPRPPR in the middle being identical. Structural differences at the residues extending this sequence to the N terminus (Arg6 in Chex1-Arg20) or C terminus (Orn in Onc72, D-Arg in Onc112, and Pro in Chex1-Arg20) may explain the slight differences observed, although these might also be related to other parts of the killing mechanism, such as penetration through the outer membrane or inhibition of the 70S ribosome (11,42). Further support that the PYLPRPRPPR motif is important for the YjiLMdtM-transporter system comes from pyrrhocoricin, which contains two substitutions (Pro1Ser and Arg7Thr) in this sequence, drosocin (four substitutions), and both apidaecins (three substitutions).…”
Section: Discussionmentioning
confidence: 99%
“…Chex1-Arg20 possesses high sequence homology to all oncocins, with the 10-residue sequence PYLPRPRPPR in the middle being identical. Structural differences at the residues extending this sequence to the N terminus (Arg6 in Chex1-Arg20) or C terminus (Orn in Onc72, D-Arg in Onc112, and Pro in Chex1-Arg20) may explain the slight differences observed, although these might also be related to other parts of the killing mechanism, such as penetration through the outer membrane or inhibition of the 70S ribosome (11,42). Further support that the PYLPRPRPPR motif is important for the YjiLMdtM-transporter system comes from pyrrhocoricin, which contains two substitutions (Pro1Ser and Arg7Thr) in this sequence, drosocin (four substitutions), and both apidaecins (three substitutions).…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the target activity allows T9W to bind to the cell membrane, which is followed by disruption of the cytoplasmic membrane, the lethal event leading to bacterial cell death. However, the exact mechanism of action of AMPs can be multiple, and recently the antimicrobial mechanism has been putatively associated with cell wall biogenesis (32), conductive ATP transport (33), and inhibition of DNA and protein synthesis (34,35). But, here, the fast killing efficiency as well as the fluorescence and the microscopic studies indeed clearly indicated that the major target of the antimicrobial action of T9W is the bacterial membrane.…”
Section: Figmentioning
confidence: 96%
“…For instance, the bacterial peptide microcin J25 (MccJ25) inhibits RNA polymerase, 8 while apidaecins (in honeybees), oncocins (in insects), and Bactenecin-7 (in mammalian cells) inhibit bacterial translation by binding to ribosomal proteins. 9,10 …”
Section: Cationic Antimicrobial Peptides (Camps) and Bacterial Resistmentioning
confidence: 99%